2007
DOI: 10.1291/hypres.30.929
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of the Addition of Losartan to Ongoing Treatment with an Angiotensin Converting Enzyme Inhibitor in Type-2 Diabetic Patients with Nephropathy

Abstract: Angiotensin converting enzyme inhibitors (ACE-Is) and angiotensin II receptor blockers (ARBs) are frequently used for the treatment for glomerulonephritis and diabetic nephropathy because of their albuminuria-or proteinuria-reducing effects. To many patients who are nonresponsive to monotherapy with these agents, combination therapy appears to be a good treatment option. In the present study, we examined the effects of the addition of an ARB (losartan) followed by titration upon addition and at 3 and 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Our studies may provide a potential mechanism involved in the superior renoprotective effects of combining an ACE inhibitor with an AT 1 receptor antagonist relative to ACE inhibitor therapy alone in patients with DN which has been reported in some clinical studies. 43,44 In addition, the presence of this ACE-independent pathway for ANGII formation may explain the continued proteinuria in some patients on maximal ACE inhibitor therapy. 45 However, the ONTARGET trial indicated that in patients with cardiovascular disease or diabetes, the combination of ANG receptor blocker and ACE inhibitor provided more adverse events without an increase in benefit compared to either monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies may provide a potential mechanism involved in the superior renoprotective effects of combining an ACE inhibitor with an AT 1 receptor antagonist relative to ACE inhibitor therapy alone in patients with DN which has been reported in some clinical studies. 43,44 In addition, the presence of this ACE-independent pathway for ANGII formation may explain the continued proteinuria in some patients on maximal ACE inhibitor therapy. 45 However, the ONTARGET trial indicated that in patients with cardiovascular disease or diabetes, the combination of ANG receptor blocker and ACE inhibitor provided more adverse events without an increase in benefit compared to either monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Increasing body of evidence implicates RAAS in DN pathogenesis. 8,15,16 This was based on the findings that ANG II induces progressive renal injury in DN, in part by increasing cellular growth and proliferation and matrix synthesis, leading to glomerular sclerosis. 17 Blockade of RAAS by ACE-I and ARBs prevented structural and functional changes in the diabetic kidney, further establishing a role for RAAS in DN.…”
Section: Introductionmentioning
confidence: 99%
“…Losartan add-on therapy resulted in a significant decrease in serum uric acid levels, although the baseline level of uric acid was within the normal range in the study patients [53]. Losartan possesses an uricosuric effect both after single and multiple doses, increasing urinary excretion of uric acid dose-dependently [54].…”
Section: Pharmacodynamicsmentioning
confidence: 76%